Managerial Skills: An Imperative for Business Education in Enhancing Nigerian Dwindling Economy - Suleiman, Lukman; Adam, Mansur Saidu; Jibrin, Usman Dahiru; Buba, Umar (American Economic & Social Review, 2017)
The main aim of this study is to determine the important of business education managerial skills in overcoming the problems of economic recession in Nigeria. Literature was extensively reviewed in relation to business education, managerial skills and economic recession, on that note the concept of business education was discussed by different literature. Furthermore, five (5) importance of business education were identified in relation to the economic development and the nation’s dwindling economy. The study went further and identifies different kind of managerial skills needed by business education students, these skills were found to be very essential in promoting the Nigerian economy and also serves as a way of eradicating the dwindling economy of any given nation.